ANALISIS DEBIT RENCANA UNTUK PERENCANAAN BANGUNAN PENGENDALI BANJIR DI DAS WAI RUATA KABUPATEN MALUKU TENGAH - Marasabessy, Syamsudin; Talakua, Silwanus Matheus; Siregar, Adelina; Osok, Rafael Marthinus (Universitas Pattimura, 2024)
The high rainfall, rapid urbanization, and the presence of impermeable surfaces have drastically increased surface runoff, overwhelming river systems with high water volumes. Changes in land use and rapid population growth further escalate flood risks. Analyzing planned discharge rates and flood control building planning becomes urgent to mitigate losses and risks caused by floods in the Wai Ruata watershed. Calculations indicate that for the Q100 Log Normal (2475.17 m3/s, the channel height is 2.50302 m, closely approximating public information (2.5 m), with a difference of 0.00302 m or 0.302 cm. This suggests that the calculated maximum flood water level based on planned discharge analysis using the rational method for Log Normal probability of 2.503 m is reasonably accurate. It can serve as a reference for flood control building design heights, potentially lasting around 100 years in the Wai Ruata watershed. Planned flood discharges in the Wai Ruata watershed are as follows: for a 2-year return period, 505.80 m3/s (Gumbel), 449.27 m3/s (Log Normal), 462.56 m3/s (Log-Pearson Type III); for a 50-year return period, 1868.80 m3/s (Gumbel), 2016.26 m3/s (Log-Normal), and 1837.18 m3/s (Log-Pearson); and for a 100-year return period, 2137.98 m3/s (Gumbel), 2475.17 m3/s (Log-Normal), 2166.93 m3/s (Log-Pearson). Gumbel planned flood discharge data can be used for a 25-year lifespan of water structures, whereas for a 100-year lifespan, Log-Normal planned flood discharge is more suitable.